Sham-Chewing in Sows Is Associated With Decreased Fear Responses in Their Offspring - Tatemoto, Patricia; Bernardino, Thiago; Alves, Luana; Zanella, Adroaldo José (Frontiers in Veterinary Science, 2019)
We hypothesized that sham-chewing expressed by the dam during gestation affects fetus programming. The goal of this study was to assess the effects of maternal sham-chewing on offspring welfare indicators, such as behavior and physiology. Sows that exhibited consistent sham-chewing on at least two of 6 days of observation (N = 7) were compared with sows that had never performed sham-chewing (non-sham-chewing sows; N = 4) during these 6 days. Salivary samples from sows and piglets were collected and cortisol concentrations were analyzed to assess the hypothalamic pituitary adrenal (HPA) axis activity as cortisol is a physiological indicator of welfare. Moreover, placental tissue was collected, right after farrowing, to assess cortisol and cortisone concentration. Piglet behavior and fear tests were performed after weaning (one couple per sow). In the fear tests, data was collected in an open field test to determine the states of fear indicators. Non-sham-chewing sows had lower concentrations of cortisol on days 91 and 92 of gestation in the morning. In addition to this, placental cortisol was higher among sham-chewing sows than non-sham-chewing sows. In the open field test, piglets born from non-sham-chewing sows demonstrated more latency to move in the arena and less activity, indicating more fear. Based on our data, we concluded that the expression of maternal sham-chewing is related to less fear in their offspring. Although stereotypies have been studied, attention has not been devoted to the effects of the prenatal period in considering a fetal reprogramming approach.